1984
DOI: 10.1159/000123959
|View full text |Cite
|
Sign up to set email alerts
|

Medial Preoptic Area, Estrogen, and the Peripubertal Desensitization to the Negative Estrogen Feedback in Female Rats

Abstract: Bilateral lesions placed in the medial preoptic area (MPOA) markedly diminished the luteinizing hormone-(LH-) and follicle-stimulating hormone- (FSH-) inhibiting effects of s.c. injected or intrahypothalamically implanted estradiol benzoate (EB) in ovariectomized immature rats. Desensitization to the negative estrogen feedback was also recorded in immature rats implanted into the MPOA with a mixture of 1 part EB and 240 or 360 parts cholesterol. Estrogen implants located in the hypothalamic ventromedial-arcuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
1
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
(27 reference statements)
1
12
1
1
Order By: Relevance
“…Former studies [10][11][12] had shown that the sensitivity to the gonadotrophin, particularly the LH-inhibiting effect of estrogen, declines substantially in immature and cyclic female rats prior to the onset of puberty and during the preovulatory phase of the ovarian cycle, respectively. The desensitization of the negative estrogen feedback is proba bly induced by increasing estrogen levels in the blood [11,13], and preliminary results [16] suggested that inhibition of the medial preoptic DA activity might be involved.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Former studies [10][11][12] had shown that the sensitivity to the gonadotrophin, particularly the LH-inhibiting effect of estrogen, declines substantially in immature and cyclic female rats prior to the onset of puberty and during the preovulatory phase of the ovarian cycle, respectively. The desensitization of the negative estrogen feedback is proba bly induced by increasing estrogen levels in the blood [11,13], and preliminary results [16] suggested that inhibition of the medial preoptic DA activity might be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The desensitization of the negative estrogen feedback is proba bly induced by increasing estrogen levels in the blood [11,13], and preliminary results [16] suggested that inhibition of the medial preoptic DA activity might be involved. The relationship between this activity and the sensitivity of the negative estrogen feedback was investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations